ASSESSMENT OF MEDICATION EFFICACY ON DETERMINANTS OF PSYCHIATRIC ILLNESS AMONG DIABETES MELLITUS PARTICIPANTS - Alex, Akza K; DR, Bharathi; GR, Nataraj; Mathew, Adarsh; SM, Tejaswini (Journal of Biomedical and Pharmaceutical Research, 2019)
Introduction: The prevalence of Diabetes Mellitus (DM) among adults has been increased considerably across the globe, and has contributed a substantial proportion in annual mortality rate. Diabetes and psychiatric disorders are having such an interface that they both influence each other in several ways. Objectives: The study was conducted to assess the prevalence, determinant factors, prescription pattern, efficacy and adverse reactions in diabetic patients associated with psychiatric illness in a tertiary care hospital. Materials and Methods: A prospective observational study was carried out for a period of ten months in General Medicine and Psychiatric Department, Basaveswara Medical College Hospital and Research centre, Chitradurga. Results: In this study, a total of 101 diabetic patients with or without co-morbidities were enrolled in the study. Among them, 27 in-patients were associated with psychiatric illness which was considered as co-morbid condition. The prevalence of psychiatric illness with diabetes mellitus was found to be 26.7% which is highly significant with the p-value (0.00). A higher prevalence was noticed with age group 41-50 years and with male gender. The common determinant factors of psychiatric illness in diabetic patients were being women, having no income, being at the age of menopause, having no physical activity, being illiterate and being single or widowed. Among the anti-diabetic drug prescriptions, there was a higher percentage of use of insulin and the most commonly prescribed drug was combination of Glimepride + Metformin (sulfonylurea and biguanide). The most commonly prescribed anti-psychotic drugs were chlordiazepoxide and alprazolam. Conclusion: The study reveals a high prevalence of psychiatric illness in diabetic patients with determinant factors of psychiatric illness in diabetic patients were being women, having no income, being at the age of menopause, having no physical activity, being illiterate and being single or widowed. Key Words: Prevalence; Determinant factors; Diabetes mellitus; Psychiatric illness